3D Graphene‐Based H2‐Production Photocatalyst and Electrocatalyst. Issue 14 (18th February 2020) - Kuang, Panyong; Sayed, Mahmoud; Fan, Jiajie; Cheng, Bei; Yu, Jiaguo
Abstract: Hydrogen (H2 ) has been deemed as the most promising and valuable alternative to nonrenewable fossil fuels. Photocatalytic and electrocatalytic water splitting are considered to be the most efficient and environmentally friendly approaches for the sustainable H2 evolution reaction (HER). Graphene with a 3D framework has been utilized for the HER due to its unique structure and properties, including its hierarchical network, large specific surface area, diverse pore distribution, outstanding light absorption ability, and excellent electrical conductivity. The large specific surface area and hierarchically porous structure of 3D graphene can not only maximize the exposure of active sites but also promote electron transfer and gas product diffusion. In addition, the free‐standing 3D graphene monolith is easily recycled compared with powder phase support, which can prevent the loss of active catalysts. By making full use of the aforementioned merits, 3D graphene‐based composite materials show great promise as high‐performance catalysts toward photocatalytic and electrocatalytic HER. In this review, recent advances in fabricating 3D graphene‐based composite materials and their applications in both photocatalytic and electrocatalytic HER are summarized and discussed. Furthermore, the current challenges and future vision associated with the design, fabrication, and integration of 3D graphene‐based composite materials toward HER are put forward. Abstract : Three‐dimensional (3D) graphene is utilized for the photocatalytic and electrocatalytic H2 evolution reaction (HER) due to its unique structure and properties, including large specific surface area, hierarchical network, and excellent electrical conductivity. 3D graphene‐based composite materials exhibit high photocatalytic and electrocatalytic HER activity. This review summarizes the recent advances of 3D graphene‐based composite materials toward photocatalytic and electrocatalytic HER.